2021
DOI: 10.1371/journal.pbio.3001490
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide CRISPR screen identifies interactors of the autophagy pathway as conserved coronavirus targets

Abstract: Over the past 20 years, 3 highly pathogenic human coronaviruses (HCoVs) have emerged—Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and, most recently, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)—demonstrating that coronaviruses (CoVs) pose a serious threat to human health and highlighting the importance of developing effective therapies against them. Similar to other viruses, CoVs are dependent on host factors for their survi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…The potent antiviral effects of CsA have also been demonstrated for SARS-CoV-2 infection in several relevant preclinical models, such as phBECs ( Sauerhering et al., 2022 ), primary human nasal epithelial cells ( Kratzel et al., 2021 ), lung donor-derived precision cut lung slices, and the above-mentioned mouse model ( Sauerhering et al., 2022 ). Given the well-established antiviral properties of CsA, it is not surprising that several FDA-approved clinical trials are underway to investigate the effect of CsA on COVID-19 outcomes in more detail ( Devaux et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potent antiviral effects of CsA have also been demonstrated for SARS-CoV-2 infection in several relevant preclinical models, such as phBECs ( Sauerhering et al., 2022 ), primary human nasal epithelial cells ( Kratzel et al., 2021 ), lung donor-derived precision cut lung slices, and the above-mentioned mouse model ( Sauerhering et al., 2022 ). Given the well-established antiviral properties of CsA, it is not surprising that several FDA-approved clinical trials are underway to investigate the effect of CsA on COVID-19 outcomes in more detail ( Devaux et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the region in Kiaa1024/Minar1/Ubtor that interacts with the Deptor protein is missing in the Kiaa1024L/Minar2 protein, the regulation of mTOR signaling is likely a function specific to the Kiaa1024/Minar1/Ubtor protein. Importantly, a recent study showed that Kiaa1024/Minar1/Ubtor is a host factor crucial for the replication of pathogenic human coronaviruses, including the SARS-CoV-2 that causes the COVID-19 (Kratzel et al, 2021). Previous studies showed that the replications of positive-strand RNA viruses including hepatitis C virus (HCV) and SARS-CoV-2 require rearranged intracellular membrane structures called replication organelle (Twu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A kinase phosphorylation study showed that SARS-CoV-2 regulated various signaling pathways, including autophagy ( Chatterjee and Thakur, 2022 ). A genome-wide CRISPR/Cas-9 knockout (KO) screening suggested that autophagy-related genes were required for SARS-CoV-2 replication ( Kratzel et al, 2021 ). More importantly, studies found that induction of autophagy is essential for the infection and replication of SARS-CoV-2 through the regulation of acute inflammatory responses ( Zhang X. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%